Cognitively flexible hypertext in an object-oriented programming course: effects of case-based instructional support on student learning - Schmidt, Cecil P. (Kansas State University, 2005)
The primary purpose of this study was to determine if a semi-automated reasoning tool that provides a set of searchable cases would improve a student’s understanding of the more difficult concepts in an object-oriented programming course. Also investigated were the relationships between the dependent variable student performance with independent variables of motivation, background knowledge, and student attitudes towards the semi-automated reasoning tool. Subjects for the study were randomly assigned from two sections of an introductory object-oriented programming course at an NCAA, Division II university in the Midwest region of the United States. Posttests were used to measure the effects of the semi-automated reasoning tool on learner competency. Background knowledge was collected through student transcripts. Motivation and student attitudes data were collected from surveys. All data were collected during the Spring 2005 semester. Data were analyzed at the p < .05 level of significance using a Wilcoxon Signed Ranks test, mixed-design ANOVA, Mann-Whitney U test, Spearman rho correlations, and thematic analysis as well as other statistical techniques. Results of the study indicated a significant difference between the group who used the semi-automated reasoning tool on complex questions and the group who did not. No significant difference was indicated between the groups on simple questions. A strong positive correlation was indicated between background knowledge and the total test scores for both content areas tested. Results of the correlational analysis between motivation and learner competencies indicated that the type of motivation, be it intrinsic or extrinsic, plays a minimal role in how students performed in this online course. Finally, students overwhelmingly felt that the semi-automated reasoning tool was an effective instructional-support tool. Results of this study suggested recommendations for practice as well as for further research. Recommendations for practice include the need for effective use of course management systems, supporting complex content through examples, using performance on background coursework when considering an online course covering complex topics, providing a case-based instructional aid for complex topics, and minimizing the economic costs in using a case-based instructional aid. Recommendations for future research include more research on relationships between background coursework and online courses, effects of a case-based instructional aid on face-to-face courses, development of overarching examples containing content from multiple computer science courses, improvements to the CBJava framework, and extending the framework to other disciplines.
Keywords: Reasoning tools; Object-oriented programming; Student performance; Education, Technology (0710); Education, Curriculum and Instruction (072)